Description of a new species of the genus Aleuropleurocelus Drews & Sampson (Hemiptera: Aleyrodidae) and a new country record for a species of the genus from Mexico - Carapia-Ruiz, Vicente Emilio (Instituto de Ecología, A.C., 2020)
In this study a new species of whitefly is described, Aleuropleurocelus mixtecus Carapia-Ruiz. The species was found on Hyptis capitata Jacq. in the Mexican states of Oaxaca and Puebla. Microphotographs of morphological structures of the puparium are provided and separation from related species of Aleuropleurocelus is briefly discussed. Additionally, the species Aleuropleurocelus cecropiae (Bondar) is herein reported for the first time from Mexico (Oaxaca, Tamaulipas). The previous report for the species is from Brazil.